Pengaruh Kualitas Tidur dan Stress terhadap Nyeri Kepala pada Siswa SMA/Sederajat di Kota Ambon - Huwae, Laura Bianca; Saija, Alessandra Flowrence; Manuputty, Amanda Gracia; Bension, Johan Bruiyf; Hataul, Is Ikhsan; Silalahi, Parningotan Yosi; Istia, Sean Samuel; Rugebregt, Joanne Marrijda; Waas, Christabella Trivosa (Universitas Islam Negeri Alauddin Makassar, 2026)
Abstract Background: Cephalgia is a condition where the sufferer will feel a sensation of pain in the head area which sometimes the sensation can spread to the face and neck. Factors that can trigger headaches are poor quality of sleep and stress. Objective: This study was conducted with the aim of the influence of sleep quality and stress on the incidence of headaches in high school students in Ambon City. Methods: This type of research is an analytical observational approach, cross-sectional design with a sample size of 367 and using accidental sampling techniques. The analysis used in this study is univariate and bivariate analysis using the chi-square test. Results: The results of this study obtained the majority of respondents who experienced headaches had poor sleep quality 10.90% and the majority of respondents who experienced headaches had moderate stress levels 8.45%. Based on the results of bivariate analysis using the Chi-square test showed that there was a relationship between sleep quality and headaches, with a value of (p =0.014) and the results of the Fisher test showed that there was a relationship between sleep quality and stress levels, with a value of (p =0.000). Further analysis using multivariate tests showed that stress levels were the most influential variables on headaches with a value of (p =0.000). Conclussion: Thus, this study shows the importance of the role of parents and schools in terms of rest and sleep and problems being faced both at school and at home. Keywords: Headache, Quality of sleep, Stress and Teenagers